Restraint stress effects on glutamate signaling protein levels in the rats’ frontal cortex: Does β1 adrenoceptor activity matter? - Zelek-Molik, Agnieszka; Gądek-Michalska, Anna; Wilczkowski, Michał; Bielawski, Adam; Maziarz, Katarzyna; Kreiner, Grzegorz; Nalepa, Irena (Frontiers in Pharmacology, 2025)
IntroductionStress-evoked dysfunctions of the frontal cortex (FC) are correlated with changes in the functioning of the glutamatergic system, and evidence demonstrates that noradrenergic transmission is an important regulator of this process. In the current study, we adopted a restraint stress (RS) model in male Wistar rats to investigate whether the blockade of β1 adrenergic receptors (β1AR) with betaxolol (BET) in stressed animals influences the body’s stress response and the expression of selected signaling proteins in the medial prefrontal cortex (mPFC).MethodsThe study was divided into two parts. In the first part, rats were exposed to RS for 3, 7, or 14 days, and the expression of glutamate signaling proteins (p(S845)/t GluA1, p(Y1472)/t GluN2B, VGLUT1, and VGLUT2) in the FC was analyzed to determine the optimal RS duration for studying the mechanisms of hypofrontality. In the second part, rats were exposed to RS for 14 days, and BET (5 mg/kg, p. o.) was administered during the last 8 days immediately after RS. The body’s stress reaction was assessed by analyzing body weight and blood levels of adrenocorticotropic hormone (ACTH) and corticosterone (CORT). Behavioral responses were evaluated using the novel object recognition (NOR) and elevated plus maze (EPM) tests. The impact of RS and BET on the expression of p(Y530)/t Fyn and p (S133)/t CREB in the mPFC was measured via Western blotting.Results and DiscussionThe first part of the study demonstrated a decreased level of glutamate receptors in rats exposed to 14 days of RS, following an initial increase observed after 7 days of RS. Results from the second part revealed that chronic RS reduced body weight, impaired recognition memory in the NOR test, augmented blood levels of ACTH, and increased the expression of p(Y530) Fyn in the mPFC. However, β1AR blockade did not alter the effects of RS on weight gain, cognitive function, or the expression of p(Y530) Fyn. β1AR blockade normalized only the blood concentration of ACTH. These results suggest that decreased Fyn kinase activity, indicated by phosphorylation at Y530, underlies the stress-evoked downregulation of GluN2B in the FC in a manner independent of β1AR activity.